Effects of Company Size, Profitability, Solvability and Audit Opinion on Audit Delay - Syaiful Bahri; Rifa Amnia (JAFFA, 2020)
This study aims to analyze the effect of company size, profitability, solvency, and audit opinion on audit delay. The population of this study is LQ-45 companies listed on the Indonesia Stock Exchange in 2017-2018, but the samples employed in this study were 31 companies. The type of research data is a quantitative data of secondary sources, which analyzed with descriptive statistical analysis, classical assumption techniques, multiple linear regression analysis, coefficient of determination R² and t test. The results of this study of solvency variables affect audit delay with a significant value of 0,000. Firm size variable has no effect on audit delay with a significant value of 0.490. The profitability variable does not affect the audit delay with a significant value of 0.098. The audit opinion variable does not affect the audit delay with a significant value of 0.313.